Tinjauan Literatur Sistematis: Masalah dan Strategi Solusi pada Live Streaming Shopping - Izzul, Muhammad; Prasetya, Heri; Subrata, Rizal (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to analyze the relationship between tax avoidance, leverage, and firm value, with transparency as a moderating variable. Tax avoidance and leverage are often employed as corporate strategies to enhance firm value, yet these strategies may also pose risks that affect stakeholder trust. In this context, transparency is considered a crucial element that can moderate these relationships, given the high market demand for accountable and transparent management practices. The study adopts a quantitative approach using secondary data obtained from the financial statements of companies listed on the Indonesia Stock Exchange (IDX) over a certain period. Data analysis was conducted using moderation regression methods to examine the interaction between tax avoidance, leverage, and transparency on firm value. The findings reveal that tax avoidance and leverage have significant effects on firm value, either positively or negatively, depending on the context. Furthermore, transparency is proven to moderate this relationship by strengthening positive effects and mitigating negative effects. These findings highlight the importance of transparency as a key factor in creating sustainable firm value. This research contributes to the corporate finance literature and serves as a reference for managers and policymakers in managing corporate strategies that focus on value enhancement while adhering to sound governance principles.